AB0380 THERAPEUTIC CHOICES AND OUTCOMES IN CHINESE PATIENTS WITH SEROLOGICALLY ACTIVE CLINICALLY QUIESCENT SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Huang, H.; Mu, L.; Zhang, Z.; Hao, Y.; Zhou, W.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) who achieved the clinical state as serologically active clinically quiescent (SACQ). It appears to account for 6–12% of all patients with SLE, but there is disagreement about whether such patients are indeed clinically stable [1-3], especially in Chinese patients. And there is no conclusion as to what kind of treatment should be taken for such patients. Objectives: To clarify the frequency and outcome of SACQ patients in lupus. And to identify factors associated with the flare of disease. Methods: Clinical data of patients diagnosed as SLE and followed in Peking University First Hospital from 2009 to 2015 were retrospectively reviewed. 682 patients with systemic lupus erythematosus who were followed up for more than 6 months at Peking University First Hospital from January 2007 to December 2015 were summarized. SACQ was defined as an at least a 6-month period with persistent serologic activity and without clinical activity and could be taking a daily dose of prednisone or equivalent less than 7.5 mg. Serologically quiescent clinically quiescent (SQCQ) patients and serologically active clinically active (SACA) patients served as control groups. Data including demographics, initial symptoms, duration to SACQ, treatments before and after SACQ, and characteristics of the flare group were analyzed. Results: Of the 682 patients, 170 were SACQ patients (24.9%), 187 were SQCQ patients, and 325 were SACA patients (47.7%). SQCQ patients (38.61±15.08 years old) were older at study start than SACQ patients (38.61±15.08 years vs. 32.09±14.35 years, p<0.001), but there was no significant difference between that of SACQ and SACA patients. 56 of the 170 SACQ patients (32.9%) experienced flare. Corticosteroids (OR 1.317, 95% CI 1.131 to 1.534; p<0.001) was an independent risk factor for flare, while antimalarials (OR 0.265, 95% CI 0.118 to 0.599; p=0.001) and immunosuppressants (OR 0.316, 95% CI 0.149 to 0.670; p=0.003) were protective factors. Conclusion: About one third of SLE patients with SACQ experience flare, more than that of patients with SQCQ. Thus, approach to prevent relapse in SACQ patient is required. Maintenance therapy of hydroxychloroquine and immunosuppressant agents may be protective and beneficial treatment strategy in these patients need further investigation. References: [1]Gladman DD, Urowitz MB, Keystone EC. Serologically active clinically quiescent systemic lupus erythematosus: a discordance between clinical and serologic features. Am J Med 1979; 66:210-5. [2]Huang WN, Tso TK, Wu HC, Yang HF, Tsay GJ. Impaired phagocytosis of apoptotic cell material in serologically active clinically quiescent patients with systemic lupus erythematosis. Int J Rheum Dis 2016; 19:1310-6. [3]Steiman AJ, Gladman DD, Ibañez D, Urowitz MB. Prolonged serologically active clinically quiescent systemic lupus erythematosus: frequency and outcome. J Rheumatol 2010; 37:1822-7. Disclosure of Interests: None declared